Relational continuity with primary and secondary care doctors: a qualitative study of perceptions of users of the Catalan national health system - Sina Waibel; Ingrid Vargas; Jordi Coderch; María-Luisa Vázquez (BMC, 2018)
Abstract Background In the current context of increasingly fragmented healthcare systems where patients are seen by multiple doctors in different settings, patients' relational continuity with one doctor is regaining relevance; however little is known about relational continuity with specialists. The aim of this study is to explore perceptions of relational continuity with primary care and secondary care doctors, its influencing factors and consequences from the viewpoint of users of the Catalan national health system (Spain). Methods We conducted a descriptive-interpretative qualitative study using a two-stage theoretical sample; (i) contexts: three healthcare areas in the Catalan national health system with differing characteristics; (ii) informants: users 18 years or older attended to at both care levels. Sample size (n = 49) was reached by saturation. Data were collected by individual semi-structured interviews, which were audio recorded and transcribed. A thematic content analysis was carried out segmenting data by study area, and leaving room for new categories to emerge from the data. Results Patients across the areas studied generally experienced consistency of primary care doctors (PCD), alongside some inconsistency of specialists. Consistency of specialists did not seem to be relevant to some patients when their clinical information was shared and used. Patients who experienced consistency and frequent visits with the same PCD or specialist described and valued having established an ongoing relationship characterised by personal trust and mutual accumulated knowledge. Identified consequences were diverse and included, for example, facilitated diagnosis or improved patient-doctor communication. The ascription to a PCD, a health system-related factor, facilitated relational continuity with the PCD, whereas organizational factors (for instance, the size of the primary care centre) favoured consistency of PCD and specialists. Doctor-related factors (for example, high technical competence or commitment to patient care) particulary fostered the development of an ongoing relationship. Conclusions Consistency of doctors differs depending on the care level as does the relevance attributed to it. Most influencing factors can be applied to both care levels and might be addressed by healthcare managers to foster relational continuity. More research is needed to fully understand the relevance patients assign to relational continuity with specialists.